(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Thomas Hardy, a prominent novelist of the Victorian era, is acclaimed for his intricate portrayal of societal ideals and personal values through his narrative style, character development and thematic exploration. This paper evaluates the placement and portrayal of these elements in Hardy's works, specifically focusing on " Far from the Madding Crowd " and "The Return of the Native." By employing realism and rich symbolism, Hardy creates authentic backdrops that mirror the societal norms and personal struggles of his characters. The complex protagonists in these novels embody conflicting societal ideals and personal values, highlighting themes of moral ambiguity and the critique of social norms. Hardy’s exploration of fate and determinism questions the extent of human agency against larger, uncontrollable forces. Furthermore, his portrayal of Victorian hypocrisy and deep empathy for his characters underscores the enduring importance of personal values over societal expectations. Through a detailed analysis of these aspects, this paper sheds light on Hardy's nuanced critique of the moral fabric of his era, offering timeless reflections on human nature and societal constructs.